Exploring Digital Parenting: A Systematic Review of Approaches, Challenges, and Outcomes - Salsabila; Hasanati, Nida; Pahmiah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Digital Parenting is a parenting style that provides clear boundaries to children about what they can and cannot do when using digital devices. These methods include teaching children about digital risks and ethics, maintaining balanced supervision of their online activities, and encouraging open communication about their online experiences. The terms used in the data search are digital parenting child, parental mediation of internet use, and social media parenting child. These terms are used to search for articles in the Web of Science, ScienceDirect, Emerald, and Google Scholar databases. From the search results, 112 journal articles were found in the period 2014-2024, then the author excluded journals that used Watase Uake. Systematic review analyzed 12 international journals (Q1, Q2, Q3, Q4). The results of this systematic observation obtained digital parenting patterns in children. Social media allows children to express themselves creatively, gives children access to information and opportunities to participate in online communities that support their interests, helps children build self-identity based on instilled values.